Sistem Penunjang Keputusan Pemilihan Aplikasi Streaming Terbaik dikalangan Remaja Menggunakan Metode SAW - Farhanah, Elsa; Agustine Prihatini, Virna; Bisabakti, Harry; Munawar, Achmad; Zuraidah, Eva (Journal of Informatics, Electrical and Electronics Engineering, 2025)
The increasing number of movie streaming services such as Netflix, Disney+ Hotstar, and Viu provides a variety of choices for users, but it also causes confusion in choosing the platform that best suits their needs, especially among teenagers. This problem is reinforced by differences in preferences regarding various aspects such as subscription price, content quality, ease of use, access speed, and variety of shows. To address these challenges, this study proposes a solution in the form of a decision support system using the Simple Additive Weighting (SAW) method. This method is used to evaluate and rank alternative applications based on five main criteria. Data were obtained from 200 adolescent respondents through an online questionnaire, and then processed using the Simple Additive Weighting normalization and weighting technique. The results showed that Netflix was ranked first with the highest preference value (0.97), followed by Disney+ Hotstar (0.88) and Viu (0.79). These findings indicate that the Simple Additive Weighting method is effective in helping users choose the best streaming application objectively and measurably based on the preferences of today's teenagers.